2011
DOI: 10.1111/j.1756-185x.2011.01635.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of HLA B27 subtypes with clinical features of ankylosing spondylitis

Abstract: B*2705 was the main subtype observed in both patient and control groups. Frequency of B*2704 was more in AS patients compared to controls. Occurrence of AS-associated uveitis was more often in B*2704-positive AS patients compared to B*2705-positive ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
17
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
7
17
1
2
Order By: Relevance
“…Some studies have indicated that HLA-B*2705-positive patients appear to be more closely associated with uveitis than HLA-B*2704; 5,6 a result opposite to our study. Consistent with our study, Chavan et al 4 reported that uveitis was observed more frequently in HLA-B*2704-positive AS patients than in HLA-B*2705-positive AS patients in an Indian population, but it did not have statistical differences. Park et al 3 and Lee et al 7 reported that there was no significant difference in the presence of uveitis between HLA-B*2704-and HLA-B*2705-positive AS patients in a Korean population.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies have indicated that HLA-B*2705-positive patients appear to be more closely associated with uveitis than HLA-B*2704; 5,6 a result opposite to our study. Consistent with our study, Chavan et al 4 reported that uveitis was observed more frequently in HLA-B*2704-positive AS patients than in HLA-B*2705-positive AS patients in an Indian population, but it did not have statistical differences. Park et al 3 and Lee et al 7 reported that there was no significant difference in the presence of uveitis between HLA-B*2704-and HLA-B*2705-positive AS patients in a Korean population.…”
Section: Discussionsupporting
confidence: 82%
“…In early axial spondyloarthritis (SpA), HLA‐B27 is associated with an earlier age of onset of inflammatory back pain, lower frequency of psoriasis, and higher frequency of radiographic sacroiliitis and magnetic resonance imaging – verified inflammation of the spine and sacroiliac joints . Several studies have attempted to establish correlations between the clinical features (age of onset, family history, joint involvement, and extra‐articular manifestations) and HLA‐B27 polymorphism, but have produced inconsistent results . This may be due to the analysis of different ethnic populations, and, more importantly, an insufficient number of individuals to ensure robust statistics.…”
Section: Introductionmentioning
confidence: 99%
“…One case of HLA‐B*27:02 was also identified among the disease‐associated B27 category. Low prevalence of HLA‐B*27:02 subtype was also observed in the previous studies carried out on Indian population . Of 81 cases in category with a potential presence of non‐AS alleles, DNA sequencing identified 80 cases of HLA‐B*27:07 and 01 case of rare subtype HLA‐B*27:19.…”
Section: Discussionmentioning
confidence: 99%
“…In Indian population, relatively higher prevalence (2.46%‐15.51%) of HLA‐B27:07 has been detected (Table ). It is to be noted that, our study did not detect HLA‐B27:06 and HLA‐B27:09, which is agreement with the studies carried out by several authors on Indian population . Along with our data, these studies indicate almost nonexistence of HLA‐B27:06 and HLA‐B27:09 alleles in our population.…”
Section: Discussionmentioning
confidence: 99%